Targeted mesenchymal stem cell and vascular endothelial growth factor strategies for repair of nerve defects with nerve tissue implanted autogenous vein graft conduits - ALARÇİN, EMİNE; KERİMOĞLU, OYA (WILEY, 2016)
Peripheral nerve gaps exceeding 1 cm require a bridging repair strategy. Clinical feasibility of autogenous nerve grafting is limited by donor site comorbidity. In this study we investigated neuroregenerative efficacy of autogenous vein grafts implanted with tissue fragments from distal nerve in combination with vascular endothelial growth factor (VEGF) or mesenchymal stem cells (MSCs) in repair of rat peripheral nerve defects. Six-groups of Sprague-Dawley rats (n=8 each) were evaluated in the autogenous setting using a 1.6 cm long peroneal nerve defect: Empty vein graft (group 1), Nerve graft (group 2), Vein graft and nerve fragments (group 3), Vein graft and nerve fragments and blank microspheres (group 4), Vein graft and nerve fragments and VEGF microspheres (group 5), Vein graft and nerve fragments and MSCs (group 6). Nerve fragments were derived from distal segment. Walking track analysis, electrophysiology and nerve histomorphometry were performed for assessment. Peroneal function indices (PFI), electrophysiology (amplitude) and axon count results for group 2 were -9.12 +/- 3.07, 12.81 +/- 2.46 mV, and 1697.88 +/- 166.18, whereas the results for group 5 were -9.35 +/- 2.55, 12.68 +/- 1.78, and 1566 +/- 131.44, respectively. The assessment results did not reveal statistical difference between groups 2 and 5 (P>0.05). The best outcomes were seen in group 2 and 5 followed by group 6. Compared to other groups, poorest outcomes were seen in group 1 (P0.05). PFI, electrophysiology (amplitude) and axon count results for group 1 were -208.82 +/- 110.69, 0.86 +/- 0.52, and 444.50 +/- 274.03, respectively. Vein conduits implanted with distal nerve-derived nerve fragments improved axonal regeneration. VEGF was superior to MSCs in facilitating nerve regeneration. (c) 2015 Wiley Periodicals, Inc. Microsurgery 36:578-585, 2016.
Keywords: MARROW STROMAL CELLS; GENE-THERAPY; RAT MODEL; REGENERATION; MICROSPHERES; GAP; PROLIFERATION; RECOVERY; SURGERY; SYSTEM